Efektivitas Media Pembelajaran Digital untuk Meningkatkan Minat Belajar Siswa di Sekolah Dasar - Mifta Huljanah; Erwin Krisman Zai (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to evaluate the effectiveness of digital learning media in enhancing elementary school students’ learning interest within the context of technological advancement in education. Digital media such as interactive videos, educational animations, and learning applications are increasingly integrated into teaching processes as a response to the demand for more innovative and adaptive education. This research discusses how digital learning media can stimulate students’ intrinsic motivation, strengthen engagement, and create a more enjoyable and contextual learning experience. The findings indicate that digital media holds significant potential to improve the quality of primary education by presenting content in an engaging and easily comprehensible manner. Despite technical challenges such as limited device availability and internet access, conceptually, digital learning media can serve as a strategic solution in reforming teaching methods in the digital age.